2020
DOI: 10.1029/2020wr027361
|View full text |Cite
|
Sign up to set email alerts
|

Land Use and Season Influence Event‐Scale Nitrate and Soluble Reactive Phosphorus Exports and Export Stoichiometry from Headwater Catchments

Abstract: Catchment nutrient export, especially during high flow events, can influence ecological processes in receiving waters by altering nitrogen (N) and phosphorus (P) concentrations and relative amounts (stoichiometry). Event-scale N and P export dynamics may be significantly altered by land use/land cover (LULC) and season. Consequently, to manage water resources, it is important to understand how LULC and season interact to influence event N and P export. In situ, high-frequency spectrophotometers allowed us to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 104 publications
(189 reference statements)
4
43
1
Order By: Relevance
“…Larger summer rainfall events tend to drive N/P ratios down (Correll et al., 1999; Green et al., 2007; Green & Finlay, 2010; Kincaid et al., 2020), which is consistent with our finding that the extreme rainfall‐runoff event of 2014 had the lowest N/P ratios in each stream. In a detailed study of the 2014 extreme rainfall event, Wilson et al.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Larger summer rainfall events tend to drive N/P ratios down (Correll et al., 1999; Green et al., 2007; Green & Finlay, 2010; Kincaid et al., 2020), which is consistent with our finding that the extreme rainfall‐runoff event of 2014 had the lowest N/P ratios in each stream. In a detailed study of the 2014 extreme rainfall event, Wilson et al.…”
Section: Discussionsupporting
confidence: 88%
“…Larger summer rainfall events tend to drive N/P ratios down (Correll et al, 1999;Green et al, 2007;Green & Finlay, 2010;Kincaid et al, 2020), which is consistent with our finding that the extreme rainfall-runoff event of 2014 had the lowest N/P ratios in each stream. In a detailed study of the 2014 extreme rainfall event, Wilson et al (2019) attribute low N/P ratios (mean = 7.1, SD = 2.1) to the efficient transport of P but not N from the watershed to the stream network via surface drainage ditches.…”
Section: N/p Ratiossupporting
confidence: 91%
See 1 more Smart Citation
“…We note that this classification scheme differs from traditional baseflow separation techniques that use graphical, geochemical, or isotopic approaches to identify and separate the proportion of the hydrograph that is comprised of baseflow and stormflow (Hooper and Shoemaker, 1986;Klaus and McDonnell, 2013). Baseflow separation techniques have shown that a large fraction of event water is derived from baseflow (e.g., Schilling and Zhang, 2004).…”
Section: Event Identificationmentioning
confidence: 99%
“…Storm export data modified from S. L. Speir unpubl. and Kincaid et al (2020).…”
Section: Agricultural Streams Are Hot Spots For Nutrient Transformation and Hot Moments For Exportmentioning
confidence: 90%